Doživljanje mestnega odprtega prostora - Bevkov trg v Novi Gorici - Bratina, Nataša (Urbani izziv, 1997)
In research on perception of open urban space, psychological and structural aspects are important, as well as social use. Social use however is most important, because open urban space and its green surfaces satisfies needs of an urban population. The psychological aspect applies to direct experiencing and perception of space, while the structural aspect proves, that public urban places are an important category in the urban structure. On the example of Bevk square, Nova Gorica, three types of analyses were carried out. With the structural analysis and evaluation, development and structure of the place were shown, its problems and qualities. The survey on public opinion utilised the method of cognitive mapping, enabled definition of the image of the square, as percieved by everyday users. With the method of time samples events on the square were observed, in different time slots and days of the week.
Keywords: mesta; Nova Gorica; trgi (urbanizem); urbana sociologija; urbanism; urbanizem